A Trigeneration System Using Triple Pressure HRSG(Energy, Exergy and Thermoeconomic Analysis) - Hadi Ghayebi; Ghader Abbaspour (مجله مدل سازی در مهندسی)
In this research, thermoeconomic analysis of a multi-effect desalination thermal vapor compression (MED-TVC) system integrated with a trigeneration system with a gas turbine prime mover is carried out. The integrated system comprises of a compressor, a combustion chamber, a gas turbine, a triple-pressure (low, medium and high pressures) heat recovery steam generator  (HRSG) system, an absorption chiller cycle (ACC), and a multi-effect desalination (MED) system. Low pressure steamproduced in the HRSG is used to drive absorption chiller cycle, medium pressure is used in desalination system and high pressure superheated steam is used for heating purposes. For thermodynamic and thermoeconomic analysis of the proposed integrated system, Engineering Equation Solver is used by employing mass, energy, exergy, and cost balance equations for each component of system. The results of the modeling showed that with the new design, the exergy efficiency in the base design will increase to 57.57%. In addition, thermoeconomic analysis revealed that the net power, heating, fresh water and cooling have the highest production cost, respectively..